ACADEMIC PHRASE USED BY ENGLISH STUDENTS IN WRITING DISCUSSION SECTION IN THESIS - Nanda Hergistha; Epi Wadison (Teaching English and Language Learning English Journal, 2024)
The objective of this research is to know the using of academic phrase in writing discussion section in students’ thesis. The design of this research using descriptive qualitative method. The data obtained using checklist table adapted by Swalles (1990). The result of this research there is the lack that found in discussion section in student thesis written by English Students’ academic year 2020. Based on the result above, the discussion section of students’ thesis is unsuffecient category.The fact of this research is expected to be an evaluation for students, it is suggested to other students to follow the academic phrase in each move by swales (1990) in writing discussion section. For further researchers, the results of this study can be a reference for the future researcher who conducts research about writing discussion section. Keywords: academic phrase, discussion section, thesis